Quantitative maternal hepatitis B surface antigen predicts maternally transmitted hepatitis B virus infection. Issue 5 (20th May 2016) - Wen, Wan‐Hsin; Huang, Chi‐Wen; Chie, Wei‐Chu; Yeung, Chun‐Yan; Zhao, Lu‐Lu; Lin, Wen‐Terng; Wu, Jia‐Feng; Ni, Yen‐Hsuan; Hsu, Hong‐Yuan; Chang, Mei‐Hwei; Lin, Lung‐Huang; Chen, Huey‐Ling
Abstract : Despite immunoprophylaxis, hepatitis B virus (HBV) transmission in highly viremic mothers remains a global health issue. Using quantitative maternal surface antigen (HBsAg) to predict HBV infection in infants has not been investigated. We enrolled 526 mother‐infant pairs with positive maternal HBsAg under current immunoprophylaxis. Maternal viral load and quantitative HBsAg were measured in the peripartum period. Infant HBsAg seropositivity for more than 6 months was defined as chronic infection. Rates of chronic infection in infants at various maternal HBsAg levels were estimated using a multivariate logistic regression model. Results showed that maternal HBsAg was positively correlated with maternal viral load (r = 0.69; P < 0.001) and accurately predicted maternal viral load above 6, 7, and 8 log10 IU/mL with an area under the receiver operating characteristic curve (AUC) of 0.97, 0.98, and 0.95. Nineteen infants were chronically infected. After adjustment for the other risk factor, maternal HBsAg level was significantly associated with risk of infection (adjusted odds ratio for each log10 IU/mL increase, 15.02; 95% confidence interval [CI], 3.89‐57.94; P < 0.001). The AUC for predicting infection by quantitative maternal HBsAg was comparable to that by maternal viral load (0.89 vs. 0.87; P = 0.459). Estimated rates of infection at maternal HBsAg levels of 4, 4.5, and 5 log10 IU/mL were 2.4% (95% CI, 0.1‐4.6; P = 0.04), 8.6% (95% CI, 4.5‐12.7; P < 0.001), and 26.4% (95% CI, 12.6‐40.2; P < 0.001). Conclusion: Quantitative maternal HBsAg predicts infection in infants as well as maternal viral load does. Antiviral therapy may be considered in pregnant women with an HBsAg level above 4‐4.5 log10 IU/mL to interrupt mother‐to‐infant transmission. (Hepatology 2016;64:1451‐1461)